Blood ties / 3. - Nix, Garth (Spirit animals, 2014)
As the Conquerors try to destroy Erdas, Meilin--fed up with waiting and ready to fight--sets off into enemy territory with her spirit animal, a panda named Jhi. Her friends Conor and Abeke aren't far behind ... but they're not the only ones.